Integrasi Pasar Bawang Merah di Kabupaten Nganjuk (Pendekatan Kointegrasi Engle-Granger) - Susanawati, Susanawati; Jamhari, Jamhari; Masyhuri, Masyhuri; Darwanto, Dwidjono Hadi (AGRARIS: Journal of Agribusiness and Rural Development Research, 2015)
This research aims to analyze price behavior, market integration, and leading market of the shallot. This research used producers and consumers monthly price data during 2009-2013. Price behavior was analyzed by coefficient of variation. Shallot market integration was analyzed by Engle-Granger model of co-integraÂtion. Granger causality was used to analyzed the leading market. The result show that shallot price behavior at producer and consumer market in Nganjuk during 2009-2013 shows a simillar movement. Shallot price trend to be low occurs on January, June, July, October, and trend to be high on March, April, July. Shallot price fluctuation at producer market is higher than consumer market. When viewing each year highÂ price fluctuation occur on August and October, while the low occur on May, June, and July. Producer and consumer market in Nganjuk already integrated or has a long run relationship, so without intervention of the goverment, market mechanism has been able to do a price adjustment if shallot price upheavals. Market leading of the shallot price in Nganjuk is consumer market.